Building a technology for mass organisation of distance learning for students in quarantine based on the Moodle platform - Oleg M. Spirin; Kateryna R. Kolos; Olena A. Kovalchuk; Olena O. Demianchuk (Academy of Cognitive and Natural Sciences, 2024)
The COVID-19 pandemic has necessitated the rapid transition to distance learning for students worldwide. This paper examines the current state of distance learning implementation in secondary schools of the Zhytomyr region in Ukraine. A survey of 2445 teachers found that most were using various software tools for distance learning without a unified learning management system. Analysis of the Moodle, Google Classroom, and "My Class" platforms showed Moodle to have significant advantages for supporting distance learning. To enable schools to leverage Moodle, an "Educational Portal for Secondary School" was developed at Zhytomyr Polytechnic State University using the Moodle platform. Based on this Moodle portal, the paper proposes a technology for the mass organisation of distance learning during quarantine. The technology combines the tools, electronic resources, course structure, and tutor competencies required for effective distance learning implementation.